CZT-1 Is a Novel Transcription Factor Controlling Cell Death and Natural Drug Resistance in Neurospora crassa - Gonçalves, A. Pedro (Genetics Society of America, 2014)
We pinpoint CZT-1 (cell death–activated zinc cluster transcription factor) as a novel transcription factor involved in tolerance to cell death induced by the protein kinase inhibitor staurosporine in Neurospora crassa. Transcriptional profiling of staurosporine-treated wild-type cells by RNA-sequencing showed that genes encoding the machinery for protein synthesis are enriched among the genes repressed by the drug. Functional category enrichment analyses also show that genes encoding components of the mitochondrial respiratory chain are downregulated by staurosporine, whereas genes involved in endoplasmic reticulum activities are upregulated. In contrast, a staurosporine-treated Δczt-1 deletion strain is unable to repress the genes for the respiratory chain and to induce the genes related to the endoplasmic reticulum, indicating a role for CZT-1 in the regulation of activity of these organelles. The Δczt-1 mutant strain displays increased reactive oxygen species accumulation on insult with staurosporine. A genome-wide association study of a wild population of N. crassa isolates pointed out genes associated with a cell death role of CZT-1, including catalase-1 (cat-1) and apoptosis-inducing factor–homologous mitochondrion-associated inducer of death 2 (amid-2). Importantly, differences in the expression of czt-1 correlates with resistance to staurosporine among wild isolate strains. Our results reveal a novel transcription factor that regulates drug resistance and cell death in response to staurosporine in laboratory strains as well as in wild isolates of N. crassa.